Interferometric scattering microscopy for the study of molecular motors - Andrecka, J; Takagi, Y; Mickolajczyk, K; Lippert, L; Sellers, J; Hancock, W; Goldman, Y; Kukura, P (Elsevier, 2016)
Our understanding of molecular motor function has been greatly improved by the development of imaging modalities, which enable real-time observation of their motion at the single-molecule level. Here, we describe the use of a new method, interferometric scattering microscopy, for the investigation of motor protein dynamics by attaching and tracking the motion of metallic nanoparticle labels as small as 20 nm diameter. Using myosin-5, kinesin-1, and dynein as examples, we describe the basic assays, labeling strategies, and principles of data analysis. Our approach is relevant not only for motor protein dynamics but also provides a general tool for single-particle tracking with high spatiotemporal precision, which overcomes the limitations of single-molecule fluorescence methods.